HUBUNGAN STATUS GIZI DAN AKTIVITAS OLAHRAGA DENGAN TINGKAT KEBUGARAN JASMANI - Bustamam Bustamam (Center for Research and Community Service (LPPM) University of Abulyatama, 2017)
Nutrient status is a body condition as a consequences of food intake and nutrient substances on certainvariable form that can be measured with certain methods. Low or abnormal nutrient status will affect tophysical fitness. Since nutrient status is one of factors that affect physical fitness level. Regular and notoverdoing sport activity will cause fitness above average and by performing sport activity exercise willcause higher physical fitness level. So that the effect to physical fitness have bigger percentage. The aim of this research is to know correlations of nutrient status and sport activity with physical fitnesslevel of eight grade student of SMP Negeri 1 Banda Aceh. This is a non-experiment research with quantitative approach and correlational design. Population in this research is all eight grade student of SMP Negeri 1Banda Aceh that amounted of 270 students. While sample collection technique that applied is cluster sampling with sample amount as big as 47 students. Instrument in this research is IMT/U for nutrient status, sportactivity questioner, TKJI test to measure physical fitness level. Data analysis that applied is logistic regression. Based on data analysis result it can be unknown that nutrient status have significant score0,024 <ρvalue (sig) 0,05, with determination coefficient as big as 42,5%, so Ho1 is rejected and Ha1 isaccepted. Thus, there is correlations between nutrient status with physical fitness as big as 42,5%. Whilesport activity have signification score 0,817 >ρvalue (sig) 0,05 so Ho2 is accepted and Ha2 rejected..Thus, it can be conclude that there is not significant correlation between nutrient status dan sport activitywith physical fitness level on eight grade student of SMP Negeri 1 Banda Aceh.